The adaptive response: I. Assessing the relative biological effectiveness of low doses of tritium. II. Determining its effect on DNA repair at a chromosomal level. - Broome, Ernest Jason. (University of Ottawa (Canada), 1999)
The adaptive response, a phenomenon sensitive to low doses of ionizing radiation, was used to assess the relative biological effectiveness (RBE) of low doses of tritium. Normal human fibroblasts (AG1522) were grown in culture to confluence and exposed to tritium beta-particles or 60Co gamma-ray adapting doses ranging from 0.10 cGy to 50 cGy. These cells, and other unexposed cells, were allowed to adapt during a 3 h, 37°C incubation prior to a challenge dose of 4 Gy of 60Co gamma-rays. Cells were replated in the presence of cytochalasin B and adaption was assessed by measuring micronucleus frequency in binucleated cells. Fluorescence in situ hybridization using whole chromosome paints (WCP) was then employed to probe the chromosome content of radiation induced micronuclei in radiation-adapted and non-adapted fibroblasts. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.